Pengembangan Dynaversity sebagai Media Pembelajaran pada Mata Pelajaran Informatika - Feryanto Daud; Manda Rohandi; Roviana H. Dai; Dian Novian; Ahmad Azhar Kadim; Arif Dwinanto (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aimed to develop an Android-based interactive learning media called DynaVersity and to determine its effectiveness in improving students' learning outcomes in the Computer Systems topic of the Informatics subject at SMK Negeri 1 Boalemo. The study employed a Research and Development (R&D) method using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects were 21 tenth-grade students. Data were collected through observations, interviews, expert validation, and pretest-posttest assessments. The validation results indicated that the learning media achieved a score of 92.6% from the media expert and 96% from the subject matter expert, both categorized as highly valid. Student responses reached 93.7%, which was categorized as very good. The effectiveness results showed an improvement in students' learning outcomes, as evidenced by the increase in the average pretest score from 65.2 to 82.8 on the posttest. Furthermore, the N-Gain analysis yielded a score of 0.50, which falls into the moderate category. The findings indicate that the developed Android-based learning media is effective in enhancing students' learning outcomes in Informatics.